(untitled) (Asian Journal of Agriculture, 2019)
Abstract. Islam MDA, Rahman MDA, Hossain MK. 2019. Effect of container and potting media on raising quality seedlings of Acacia auriculiformis in the nursery. Asian J Agric 3: 26-32. This study elucidates the effect of container and potting media on raising quality seedlings of Acacia auriculiformis in the nursery of the Institute of Forestry and Environmental Sciences, University of Chittagong to find out a suitable container and potting media for raising large scale quality seedlings. The seedlings were evaluated by testing five containers and seven potting media treatments for eight months. A Completely Randomized Block Design (CRBD) was adopted for the study with three replications for each treatment. The Analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) was tested for the analysis to explore the possible treatment variations. However, the study reveals nodulation with growth parameters; shoot and root dry biomass production and quality index were highest in 20 cm × 15 cm size polybags whereas the highest root length and shoot-root ratio was observed in 15 cm × 10 cm and 15 cm × 13 cm size polybag respectively. Considering the potting media, highest nodulation, growth parameters, shoot dry and fresh weight, shoot- root ratio and biomass were found in combination of soil + cow dung + phosphorus (0.16 g/polybag). Highest root length, root fresh and dry weight, and quality index were found in the combination of soil + cow dung (3:1). Therefore, it is recommended that containers of 20 cm × 15 cm size polybag and with a potting media of soil + cow dung + phosphorus (3 parts soil, 1 parts cow dung + 0.16 g/polybag) combination produce quality A. auriculiformis seedlings in the nursery.